Perspectives on ROCK2 as a Therapeutic Target for Alzheimer’s Disease - Weber, Audrey J.; Herskowitz, Jeremy H. (Frontiers in Cellular Neuroscience, 2021)
Rho-associated coiled-coil containing kinase isoform 2 (ROCK2) is a member of the AGC family of serine/threonine kinases and an extensively studied regulator of actin-mediated cytoskeleton contractility. Over the past decade, new evidence has emerged that suggests ROCK2 regulates autophagy. Recent studies indicate that dysregulation of autophagy contributes to the development of misfolded tau aggregates among entorhinal cortex excitatory neurons in early Alzheimer’s disease. While accumulation of tau oligomers and fibrils is toxic to neurons, autophagy facilitates degradation of these pathologic species, and represents a major cellular pathway for tau disposal in neurons. ROCK2 is expressed in excitatory neurons and pharmacologic inhibition of ROCK2 can induce autophagy pathways. In this mini review, we explore potential mechanisms by which ROCK2 mediates autophagy and actin dynamics and discuss how these pathways represent therapeutic avenues for Alzheimer’s disease.